Analisis Peran Guru Bimbingan Konseling dalam Mengoptimalisasi Prososial, Disiplin, dan Motivasi Siswa di MAN 1 Sarolangun - Arian Aprizan (Universitas Mathla'ul Anwar Banten, 2026)
This study aims to analyze the role of Guidance and Counseling (GC) teachers in shaping students’ character at MAN 1 Sarolangun, particularly in the aspects of prosocial character, discipline, and learning motivation. This study employed a qualitative method using observation, interviews, and documentation as data collection techniques. The findings indicate that GC teachers play a significant role in students’ character development through an eclectic and transformational approach. The eclectic approach is reflected in the use of various service strategies, including individual counseling, group guidance, character development programs, as well as religious and persuasive approaches adjusted to students’ needs. Meanwhile, the transformational aspect is evident in the teachers’ efforts to encourage behavioral changes toward improved discipline, strengthened prosocial character, and increased learning motivation. The study also found that the implementation of counseling services contributed positively to strengthening students’ character within the madrasa environment, although challenges remain in the internalization of values and the consistency of students’ behavior in daily life. Therefore, the role of Guidance and Counseling teachers is considered a strategic component in supporting the success of character education at MAN 1 Sarolangun